Repeatability of superovulatory response to successive FSH treatments in Merino sheep - Bruno Galarraga, María Macarena (2014)
The efficiency of a multiple ovulation and embryo transfer program depends on the recovery of a large number of viable embryos per donor ewe at each successive superovulatory treatment. Embryo production, however, is characterized by high individual variability in the ovarian response to hormonal treatment. This study evaluated the repeatability of ovarian response and embryo recovery following three successive superovulatory treatments in 10 four-year-old Merino ewes over a short period of time. Oestrus was synchronized using an intravaginal progesterone pessary inserted on Day 0 and removed on Day 14. FSH was administered to induce superovulation in declining doses twice daily over 3 days as 2(18 + 14 + 8) = 80. mg total commencing on Day 12 after pessary insertion. A dose of 200. IU eCG was administered at pessary removal. Vasectomized rams were used for heat detection and laparoscopic AI was performed 12. h after oestrus detection. Surgical embryo recovery was performed at Day 8 after pessary removal, following which prostaglandin was administered and the next superovulatory procedures began 5 days later giving a 27-day interval between embryo recoveries. Ovulation rates (mean. ±. SEM) for the three successive superovulatory treatments were 13.8. ±. 2.2, 12.1. ±. 2.2 and 12.0. ±. 2.2 (NS); and total embryos recovered were 8.3. ±. 1.4, 6.3. ±. 1.4 and 3.9 ± 1.4 (P= 0.06), respectively. Consequently, the embryo recovery rates declined from 66.1. ±. 7.5% for the first recovery to 41.4. ±. 7.5 and 34.5. ±. 7.5% for the second and third recoveries (P= 0.04). The repeatability was r= 0.84 (P< 0.05) for ovulation rate, r= 0.13 (NS) for total number of embryos and r= 0.09 (NS) for number of grade 1 and 2 embryos. The study showed that an average of 16.3. ±. 2.6 grades 1 and 2 embryos per donor ewe could be recovered over a period of 2.5 months. The high repeatability of ovarian response to successive superovulatory treatments would have to be associated with a high level of repeatability for the number of transferable embryos recovered for it to be used as a criterion for selecting donors on the basis of their response to the first hormonal treatment.